Climate change communication in India: A study on climate change imageries on Instagram - Sreelekshmi Beena; S. Anand Lenin Vethanayagam (Communications in Humanities and Social Sciences, 2023)
The rising accessibility of mobile phones and the proliferation of social media have revolutionized the way climate change has been communicated. Yet, the inherent invisibility and temporal complexities of climate change pose challenges when trying to communicate it on visual media platforms. This study employs visual content analysis to investigate how environmental non-government organizations (NGOs) in India address these limitations on their Instagram pages. Four environmental NGOs based in India were selected, and their thirty most recent Instagram posts related to climate change were analyzed based on imagery type, subject, context and themes. The findings revealed that these NGOs employed a diverse range of climate change imageries, often accompanied by overlaying texts, to traverse the lack of standardized visual tropes. Moreover, it is noted that a significant majority of analyzed Instagram imageries following the visual principles advocated by Climate Outreach emerged from one single NGO account, suggesting potential variations in the visual communication strategies among different NGOs.